REGENERATIVE POTENTIAL AND PHYTOCHEMICAL DIVERSITY AMONG FIVE ACCESSIONS OF BACOPA MONNIERI (L.) WETTST - A. KOUL,; M. KUSHWAHA,; A.P. GUPTA,; S. MALLUBHOTLA, (International Journal of Pharma and Bio Sciences, 2015)
Distant geographical niches have shown a pronounced effect on variability in organoleptic characteristics as well as biochemical constituents between accessions of a given plant species, keeping this in view the present study has been designed using five accessions of memory enhancing herb Bacopa monnieri. Maximum friable callus was regenerated in accession BM003 (GI: 54.61 ± 0.11) on B5 media supplemented with 2,4-D (1.0 mg l-1) while, MS media with NAA (1.0 mg l-1) + BAP (0.5 mg l-1) resulted in maximum indirect organogenesis in BM003 (GI: 99.58 ± 0.06). Biochemical profiling proved the qualitative differences in the carbohydrate, alkaloid, saponin and terpenoid contents in leaf, shoot and root samples of all accessions. LC-ESI-MS analysis revealed that the shoot extract of accession BM002 (7236.38 µg gm-1) contains highest Bacoside content as compared to that of its root extract (1015.32 µg gm-1) and the shoots had higher Bacoside contents as compared to the roots.